Visceral Adiposity Index in Breast Cancer Survivors: A Case-Control Study - Elías Cardoso-Peña; Alexandra E. Soto Pina; Ángel Gómez Villanueva; Gerardo Emilio López Chavez; Pablo Ramírez Martínez; Humberto Ramírez Montoya; María Guadalupe Berumen Lechuga; Alejandra Donají Benitez Arciniega; María de Lourdes Alarcón Fortepiani; Roxana Valdés Ramos; José de Jesús Garduño García (International Journal of Endocrinology)
Background. Breast cancer (BC) is the first cause of cancer morbidity and mortality in women. This disease has been linked to obesity; however, it is not clear how fat accumulation affects women who survive breast cancer. Although the visceral adiposity index (VAI) is a marker of cardiometabolic risk and adipose tissue dysfunction, it is not clear how it changes in breast cancer survivors. The aim of this investigation was to compare VAI in women with and without breast cancer. Methods. A case-control cross-sectional study was conducted on women who were BC survivors and women without the history of BC (control group). Body composition was assessed using electrical bioimpedance while VAI by means of waist circumference (WC), body mass index (BMI), triacylglycerols (TG), and high-density lipoprotein cholesterol (HDL-C). Results. 49 women in the BC survivor group and 50 in the control group. WC was wider in the survivor group as regards control (93.65 ± 10.48 vs. 88.52 ± 9.61 cm) (p=0.025); at once, TG and VAI were significantly higher for the survivor group (243.55 ± 199.84 vs. 159.84 ± 75.77) (p=0.007) and (11.03 ± 11.15 vs. 6.41 ± 3.66) (p<0.005), respectively. Body composition parameters were similar in both groups. Conclusions. VAI is higher in women who are BC survivors in comparison with controls matched by age and bodyweight.